Legal description of violations of competition legislation in air industry: domestic and international experience - Корчак, Наталія Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
On the basis of analysis of information of domestic and international experience of bringing in to responsibilityfor violation of competition legislation, an attempt to select the most widespread types of offences in airindustry for the last three years is done in the article.